Absorption line asymmetry: Speed-dependent effects observed from coherent transients on the 86 GHz line of HC15N in collision with polar and diatomic molecules and with rare gases. (September 2021) - Rohart, François
Highlights: Lineshape asymmetries: comparison of hypergeometric and quadratic SD-Voigt profiles. HCN relaxation induced by polar and diatomic molecules and by rare gases. Temperature dependence of broadening and frequency-shifting rates and of SD-parameters. Consequences of e.m. field frequency instabilities on absorption lineshapes. Lineshape analysis from time domain coherent transients (optical precession). Abstract: The shape of the J = 0→1 rotational line of HC 15 N at 86 GHz has been recorded in collision with various polar and diatomic molecules and with all rare gases within the 135-300 kelvin temperature range. The coherent transient technique employed, optical precession in the time domain, has revealed as very propitious to analyze departures observed from the Voigt profile. First, a detailed analysis of frequency-instabilities of the electromagnetic source has been done and their consequences on observed signals are discussed in details. Then, it has been clearly evidenced that Voigt profile departures result from the speed-dependence (SD) of collisional broadening and frequency-shifting rates, a feature responsible of narrowing and asymmetry of lineshapes, respectively, in the frequency domain. In contrast, it appears that velocity/speed changing collisions have a negligible influence. From a comparison of the hypergeometric SD-Voigt profile with the quadratic SD-Voigt profile, it is shown the latter could be inappropriate in case of SD-frequency-shifts. So, experimental records have been fitted using the asymmetric hypergeometric SD-Voigt profile and temperature dependences have been analyzed. Finally and as required for inclusion in databases, results are also given using Hartmann-Tran profile parameters.